Personality Distance and Economic Activity - Niszczota, Paweł (Studia Oeconomica Posnaniensia, 2015)
Building on the similarity-attraction hypothesis I examine whether differences in the personalities of inhabitants from interacting countries affect the level of economic activity between them. To do this I investigate whether both aggregated and nonaggregated differences in personality scores of average inhabitants from two countries have the potential to explain variation in the level of trade, foreign portfolio investment, mergers and acquisitions, and cross-listings between these countries. Results show that only the number of cross-listings is negatively and statistically significantly related to personality distance. I discuss possible reasons for the lack of support (in general) for the hypothesized relationship.